The Role of the Economic Sector Growth in the Province Maluku - KEMBAUW, Esther; SAHUSILAWANE, Aphrodite Milana; SINAY, Lexy Janzen; BATLOLONA, John Rafafy (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
Regional economic development is a process of local government and the entire community to manage the various resources available. One measure of the success of economic development is viewed from the economic growth. The economic growth of an area can be seen from the value of GDP of the area. The imbalance in the contribution of each sector to the GDP value of Maluku province indicates the persistence of disparities in economic sectors Maluku province. The gap is meant income gap, employment gap in each sector that will always be a problem if left continuously. This study aims to analyze which sectors that have relevance to the forward and backward linkages that can be known which sector became the leading sectors, potential and backward in Maluku province. Then with the input output analysis can know which sectors have the most impact on output, income and employment opportunities for other sectors and to identify changes that occur in each sector if there is a change in the economic structure in Maluku province. Of the three analyses, we can conclude which sector most positive influence on other economic sectors in the province of Maluku.